Survey Consultation: Regional Needs and Priorities for Climate Information Services - List, Geneva; Zebiak, Stephen E.; Rose, Alison (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Survey for regional stakeholder consultation